CONSUMER PERCEPTIONS OF GEOGRAPHICAL INDICATIONS, BRANDING, AND INTELLECTUAL PROPERTY IN THE AGRICULTURAL SECTOR - Ostojić, Bojana; Petrović, Vesna; Despotović, Danijela (Economics of Agriculture, 2025)
This paper examines the role of geographical indications and branding in shaping consumer perceptions of quality in agricultural products, as well as attitudes toward intellectual property protection. A quantitative survey was conducted through an online questionnaire in September 2025, involving 214 respondents from Serbia. Socio demographic variables such as gender, age, education, place of residence, and frequency of agricultural product consumption were considered to account for differences in consumer attitudes. The results reveal generally low levels of support for geographical indications, branding, and intellectual property protection in agriculture, with mean values consistently below 3 across all measurement scales (ranging from 2.37 to 2.71). However, statistical test results showed that the frequency of consumption significantly influences perceptions of branding, while education and place of residence do not exert a significant effect. These findings provide valuable insights for producers and policymakers in strengthening branding strategies, safeguarding traditional products, and fostering sustainable rural development.